Expansive Leadership - Poonamallee, Latha (Tantor Media, Inc., 2021)
The structured twenty-eight-day mindfulness and contemplative journey presented in this book will help aspiring and current leaders to clarify their identities, and identify and reflect on their mental models to become more expansive leaders. The present moment demands new ways of being, doing, and relating with the world. To meet this moment, we need fresh, collective, inclusive, and interdependent models of leadership and new approaches to leadership development. This book goes beyond the "McMindfulness" often seen in mindful leadership books, to offer a multi-faceted approach to develop a more interconnected sense of self and interdependence-centric mindsets needed for expansive leadership, through mindfulness practice. Through this practice, leaders can cultivate the ability to make deliberate choices using slow thinking and overcome any unconscious and implicit biases that are the result of fast-thinking processes. Anchored in insights from over ten years of teaching mindfulness-based leadership development courses, this book is an invitation to explore how to be a leader in an expansive, inclusive, robust, and resilient way. The listener will have an opportunity to define and refine their identity, uncover their personal mental models, and conclude by developing their own leadership philosophy.